2017
DOI: 10.1007/s00586-017-5086-7
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the thoracic spine completely removed by total spondylectomy after neoadjuvant denosumab therapy

Abstract: These findings support that GCTB stromal cells survived around the newly formed woven bone after long-term denosumab treatment and total surgical resection of such primary spinal lesions as the gold-standard treatment, even following administration of denosumab. Surgeons should note that prolonged adjuvant denosumab therapy may increase the difficulty of performing a posterior-approach total en bloc spondylectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…A critical review of these published studies identified 60 studies that met the inclusion criteria for the present meta-analysis (Table 1). 11,12,44,60 -116 The www.clinicaltrials.gov website showed 7 ongoing studies of denosumab in the treatment of GCTB. The majority of the studies examined for this meta-analysis were case reports, case series studies, and nonrandomized, uncontrolled, open-label phase II studies (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical review of these published studies identified 60 studies that met the inclusion criteria for the present meta-analysis (Table 1). 11,12,44,60 -116 The www.clinicaltrials.gov website showed 7 ongoing studies of denosumab in the treatment of GCTB. The majority of the studies examined for this meta-analysis were case reports, case series studies, and nonrandomized, uncontrolled, open-label phase II studies (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most participants in the studies analyzed were from case series studies, followed by the nonrandomized, uncontrolled, openlabel phase II studies, and then case reports. 90 Tsukamoto et al 92 Matcuk et al 106 Bilgetekin et al 62 Xará-Leite et al 65 Marinova et al 68 Kinoshita et al 70 Osaka et al 71 Liu et al 74 Wu et al 84 Law et al 85 Satcher et al 87 Yonezawa et al 89 Bardakhchyan et al 91 (continued) Menon et al 95 Inoue et al 97 Cavalcante et al 99 Yamagishi et al 100 Kajiwara et al 101 Nakazawa et al Setsu et al 103 Aponte-Tinao et al 104 Park et al 105 Vaishya et al 107 Gossai et al 109 Watanabe et al 110 Mattei et al 111 Hakozaki et al 112 Aghaloo et al 113 Rossi et al 114 Akaike Abbreviation: SD, standard deviation a The majority of study participants were women, and the median age was 30. There was no significant difference in the duration of treatment and follow-up time.…”
Section: Proportion Of Participants In Each Study Design Typementioning
confidence: 99%
“…We reviewed studies on aggressive GCT published over the past 20 years according to PRISMA statement, and 52 studies were involved ( Figure 10 ). 15 - 66 There were 60 patients with 53 CT scans and 39 MRI scans, of whom 21 patients underwent enhanced scans simultaneously. The typical and atypical features were summarized according to the diagnostic standards in the present study ( Table 2 ) and the frequency of the features was similar.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have suggested that bone cement injection induces cytotoxic tumor necrosis [22, 23]. Trials of monoclonal antibody therapy for GCT, including denosumab as neoadjuvant chemotherapy, have shown favorable effects in combination with surgical downstaging, even in cases with extraosseous epidural extent [24]. Refai et al [19] and Mahajan et al [25] reported a combined approach in two cases that used preoperative embolization of the tumor vascular supply, followed by complete resection and postoperative radiotherapy, with no recurrence at 12 months after surgery.…”
Section: Discussionmentioning
confidence: 99%